Timelike bound orbits and pericenter precession around black hole with conformally coupled scalar hair - Qi Qi; Xiao-Mei Kuang; Yong-Zhuang Li; Yu Sang (European Physical Journal C: Particles and Fields, 2024)
Abstract We investigate the geodesic motions of timelike particles around a static hairy black hole with conformally coupled scalar field. We mainly focus on the effects of the scalar charge and electric charge on the marginally bound orbits (MBO), innermost stable circular orbits (ISCO) and on the precessing orbits around this black hole. Our results show that both the scalar and electric charges suppress the energy as well as the angular momentum of the particles in the bound orbits. Then, we study the relativistic periastron precessions of the particles and constrain the charge parameters by employing the observational result of the S2 star’s precession in SgrA*. It is found that the constraints on the charge parameters from S2 star’s motion are tighter than those from black hole shadow. Finally, we analyze the periodic motions of the particles and figure out samples of periodic orbits’ configurations around the hairy black hole.